Quality changes in reared, hot-smoked meagre (Argyrosomus regius Asso, 1801) during chill storage at 4 ± 1 °C - BİLGİN,Şengül (2019)
Abstract The aim of this study was to investigate quality and nutritional changes in reared meagre after the use of hot smoking technology. Hot smoking method was applied to the meagre and the resulting smoked fish were used to produce fillets, which were stored in refrigerator after being vacuum packed. As a result of chemical component analysis, it was seen that the fat content was low. In particular, the PUFA contents of meagre were found to be very high (35.53% Control). During storage, changes in fatty acid composition and the chemical, sensory and microbiological changes were analyzed. In terms of the chemical quality indicated, pH, TBA and TMA values ​​didn’t exceed limit values during the storage of both fresh (6.25, 0.44 mgMDA/kg and 4.50 mg/100g) and hot smoked fish (6.23, 1.12 mgMDA/kg,5.57mg/100g respectively), ​​but the TVB-N value exceeded limit values at day 56 of storage for hot smoked samples (39.50mg/100g). According to microbiological limit values accepted for seafood ​​fresh and hot smoked meagre lost consumption characteristics after day 7 and day 35 of storage, respectively. Meagre was determined to be appropriate for the hot smoking process, based on the quality analyses, especially sensory analyses.